If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2*x)/2 = -19/2 // + -19/2
(2*x)/2-(-19/2) = 0
(2*x)/2+19/2 = 0
x+19/2 = 0 // - 19/2
x = -19/2
x = -19/2
| 6g-6g-5-9= | | 23=n/-8 | | 75x-255=23x*286 | | 1.5x+17.2=2.3x+9.6 | | -4x+13=3(x-8)+4 | | 2n+2=98 | | 8-5(4-3z)=2(4-z)-8 | | 8(x+4)-3x=2(x+16)+3x | | 3m^2*5m+2=0 | | 2x=-5+(-14) | | ln*(x+44)+ln*(x+2)=ln*43 | | y=2.3x+9.6 | | ax-b=z | | 6x+108=10x-12 | | -27=5w-2 | | x/9(x-27y-4) | | 6y+8=-22 | | -13(y-60)=y+(-59) | | y=1.5x+17.2 | | 2v+8=-2 | | 3+11y=-6.5+1.5y | | log(x)=0.33 | | 0.19y+0.09(y+9000)=2770 | | 2(4x-2.9)=4x-5.8 | | X=3+11y | | Yx^5-19=106 | | -0.2x+7.28=-0.7x+3.78 | | -4*(-1)*8= | | 20y+8=12 | | 55+5x=130 | | -(4-m)=-(9m+4) | | 0.60x+0.40x(100-x)=50 |